2021
DOI: 10.3389/fnut.2021.688897
|View full text |Cite
|
Sign up to set email alerts
|

Solanaceous Vegetables and Colorectal Cancer Risk: A Hospital-Based Matched Case-Control Study in Northeast China

Abstract: Background: Dietary factors are regarded as an essential influence in changing colorectal cancer (CRC) risk. However, there is no clear conclusion of the relationship between solanaceous vegetables and colorectal cancer at present. The study aimed to evaluate the intake of solanaceous vegetables in relation to colorectal cancer risk among the Northeast Chinese population.Methods: We carried out a hospital-based case-control study in three hospitals in Northeast China from 2009 to 2011. The study finally includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…To date, there have been scarce studies investigating the anticancer activities of tomato seeds. However, tomato intake was reported to reduce the risk of colorectal cancer, which might be due to the inhibition of tumor cell proliferation. , Also, tomato glycoalkaloid found in tomato peels could inhibit the growth of the colon cell line of HT29 . Taking together, tomato processing waste materials could be used as essential raw materials for valuable nutraceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been scarce studies investigating the anticancer activities of tomato seeds. However, tomato intake was reported to reduce the risk of colorectal cancer, which might be due to the inhibition of tumor cell proliferation. , Also, tomato glycoalkaloid found in tomato peels could inhibit the growth of the colon cell line of HT29 . Taking together, tomato processing waste materials could be used as essential raw materials for valuable nutraceuticals.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 case-control studies, eight studies were conducted in Asia ( 25 – 28 , 30 33 ), two in Europe ( 10 , 29 ), two in North America ( 9 , 23 ), one in Africa ( 24 ), and one in South America ( 22 ). As to study design, most of these studies were population-based controls ( 9 , 22 , 23 , 26 , 30 , 33 ), and the remaining six studies used a hospital-based case-control design ( 10 , 24 , 25 , 27 29 , 31 , 32 ). Moreover, seven studies examined the association between chili pepper intake and the risk of GC ( 9 , 10 , 22 , 23 , 25 , 27 , 28 ), three on CRC ( 29 , 32 , 33 ), and four on EC ( 24 , 26 , 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…As to study design, most of these studies were population-based controls ( 9 , 22 , 23 , 26 , 30 , 33 ), and the remaining six studies used a hospital-based case-control design ( 10 , 24 , 25 , 27 29 , 31 , 32 ). Moreover, seven studies examined the association between chili pepper intake and the risk of GC ( 9 , 10 , 22 , 23 , 25 , 27 , 28 ), three on CRC ( 29 , 32 , 33 ), and four on EC ( 24 , 26 , 30 , 31 ). In terms of the assessment methods of exposure, five studies ( 9 , 22 24 , 31 ) used the FFQ, while nine studies used frequency-reported questionnaires ( 10 , 25 – 30 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations